2000
DOI: 10.1053/ejvs.1999.1008
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Normal and Atherosclerotic Carotid Arteries

Abstract: carotid wall areas with small increase in IMT have a poor correlation with carotid artery stiffness. The carotid stiffness increases in areas with marked wall thickening and particularly in segments with plaque. The simultaneous study of vessel-wall elastic behaviour with IMT and plaque changes may increase our understanding of atherosclerotic progression and wall remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 22 publications
3
28
0
1
Order By: Relevance
“…stiffer with increasing age. 22 In the present study plaques from older patients were found to have decreased total elastin and decreased intermediate elastin forms. The collagen/ elastin ratio and the stiffness of the plaques are therefore expected to increase with age, a result in accordance with earlier studies.…”
Section: Discussionsupporting
confidence: 51%
“…stiffer with increasing age. 22 In the present study plaques from older patients were found to have decreased total elastin and decreased intermediate elastin forms. The collagen/ elastin ratio and the stiffness of the plaques are therefore expected to increase with age, a result in accordance with earlier studies.…”
Section: Discussionsupporting
confidence: 51%
“…IMT was the only factor independently contributing to the variation of b, and the only variable other than BP independently affecting distensibility. Interestingly, several studies in adults mostly observed no, or weak, relationships between arterial distensibility and IMT [43][44][45][46]. It has been suggested that carotid wall thickness may affect arterial elasticity to a major degree only in the presence of extensive atherosclerotic plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported a significant correlation between EM and M-IMT at CCA in vascular patients with M-IMT Ͼ0.88 mm and with plaques but not in normal subjects. 26 There is no previous report of the correlations between carotid distensibility and carotid IMT in different segments as we examined in this study. We recently demonstrated significant genetic contribution to IMT and genetic correlation between IMT and obesity in a subset (nϭ440) of the current cohort.…”
Section: Discussionmentioning
confidence: 72%